REFLECTIVE COMPETENCE IN SURDOPEDAGOGUE TRAINING: A FRAMEWORK FOR ENHANCING PROFESSIONAL SELF-ANALYSIS AMONG PRE-SERVICE TEACHERS OF THE DEAF - Rakhimova Munira Ilkhamovna (Journal of Applied Science and Social Science, 2026)
This study investigates the development and validation of a multi-dimensional framework for enhancing reflective competence among pre-service surdopedagogues — specialist teachers working with deaf and hard-of-hearing children. Grounded in the theoretical traditions of Schön's reflective practice, Vygotsky's activity theory, and contemporary competence-based approaches to teacher education, the study proposes a four-dimensional model of professional reflection specifically contextualised for surdopedagogical practice: cognitive, communicative, personal, and anticipatory reflection.